2021
DOI: 10.1101/2021.06.23.449568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased lung cell entry of B.1.617.2 and evasion of antibodies induced by infection and BNT162b2 vaccination

Abstract: The delta variant of SARS-CoV-2, B.1.617.2, emerged in India and has subsequently spread to over 80 countries. B.1.617.2 rapidly replaced B.1.1.7 as the dominant virus in the United Kingdom, resulting in a steep increase in new infections, and a similar development is expected for other countries. Effective countermeasures require information on susceptibility of B.1.617.2 to control by antibodies elicited by vaccines and used for COVID-19 therapy. We show, using pseudotyping, that B.1.617.2 evades control by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In another recent study, it has been reported that infection with B.1.617.2 variant could be controlled by antibodies induced due to prior infection or BNT162b2 vaccination, but with lower efficacy than the B.1.351 variant. This study further demonstrated that B.1.617.2 variant has greater lung cell entry and cell to cell fusion, indicating its higher lung infection capacity [30]. Although various studies have shown the phenotypic effect of the mutations, and increased transmissibility, limited data exist on comparative dynamics, molecular interactions, and changes in energetics due to these crucial mutations in the RBD domain of the spike protein of various mutants.…”
Section: Introductionmentioning
confidence: 51%
“…In another recent study, it has been reported that infection with B.1.617.2 variant could be controlled by antibodies induced due to prior infection or BNT162b2 vaccination, but with lower efficacy than the B.1.351 variant. This study further demonstrated that B.1.617.2 variant has greater lung cell entry and cell to cell fusion, indicating its higher lung infection capacity [30]. Although various studies have shown the phenotypic effect of the mutations, and increased transmissibility, limited data exist on comparative dynamics, molecular interactions, and changes in energetics due to these crucial mutations in the RBD domain of the spike protein of various mutants.…”
Section: Introductionmentioning
confidence: 51%
“…In their very recent study, Arora et al explored the internalization efficacy of the Delta spike variant on various cell lines [ 15 ]. In those studies, Caco-2 and Calu-3 cells, compared to 293T, exhibited a markedly increased cellular uptake of the Delta spike variant.…”
Section: Resultsmentioning
confidence: 99%
“…The Delta’s mutations result in multiple replacements of neutral or negatively charged amino acids with positively charged ones [ 13 ]. On the other hand, the spike protein’s shift towards a positive electrostatic potential does not lead to increased affinity towards ACE2, a cell surface protease widely recognized as the main cell entry receptor for SARS-CoV-2 [ 14 , 15 , 16 , 17 ]. A recent study showed that mutating the intracellular domain of ACE2 does not affect the intracellular entry of SARS-CoV-2, suggesting that the internalization of the virus is driven by ACE2 independent receptors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used a vesicular stomatitis virus-based pseudotyped virus assay to analyse neutralisation. 6 This study was approved by the Internal Review Board of Hannover Medical School. All participants gave written informed consent.…”
Section: Sars-cov-2 Delta Variant Neutralisation After Heterologous Chadox1-s/bnt162b2 Vaccinationmentioning
confidence: 99%